Attitudes of physicians and scientists to peer reviewing for biomedical journals: A survey from the Middle East and Africa - Beshyah, Salem; Ali, Khawla; Hafidh, Khadija (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Introduction: Peer review is vital to the scientific publishing process. However, the present system has been criticized and accused of bias, lack of transparency, and failure to detect significant breakthroughs. Peer reviewers usually work pro bono, and their efforts are not formally acknowledged. Some journals have difficulty finding appropriate reviewers who can complete timely reviews, resulting in significant publication delay. Materials and Methods: An online survey of a convenience sample of clinicians and biomedical scientists from the Middle East (107) and Africa (69) was conducted to explore why reviewers decline to review and to ascertain their opinions on reviewer incentives. Items were scored on 5-point Likert scales, with low scores indicating low importance or low agreement. Results: One hundred and seventy two respondents provided adequate responses for analysis. Factors rated most highly in importance for the decision to accept to review a paper included contribution of the paper to the subject area (69.8%), the relevance of the topic to own work (66.0%), and desire to keep up to date with research (63.8%). The most highly rated factor that was important in the decision to decline to review was conflict with other workloads (69.4%), followed by low quality of submissions and tight time scale (65.8% for both), and lack of interest (65.1%). Most respondents agreed that financial incentives would not be effective when time constraints are prohibitive. However, reviewers agreed that nonfinancial incentives might encourage reviewers to accept requests to review: annual acknowledgment on the journal's website (78.5%), more feedback about the outcome of the submission (74.3%) and quality of the review (73.0%), appointment of reviewers to the journal's editorial board (69.1%), and being offered free subscription to the journal content (68.7%). Conclusions: Reviewers are more likely to accept to review a manuscript when it is relevant to their area of interest. Lack of time is the principal factor in the decision to decline. Reviewing should be formally recognized by academic institutions, and journals should acknowledge reviewers' work.
Keywords: Developing regions; medical journalism; peer review; research; scholarly publishing